The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/cryst8070296
|View full text |Cite
|
Sign up to set email alerts
|

Deposition Technologies of High-Efficiency CIGS Solar Cells: Development of Two-Step and Co-Evaporation Processes

Abstract: Abstract:The two-step process including the deposition of the metal precursors followed by heating the metal precursors in a vacuum environment of Se overpressure was employed for the preparation of Cu(In,Ga)Se 2 (CIGS) films. The CIGS films selenized at the relatively high Se flow rate of 25 Å/s exhibited improved surface morphologies. The correlations among the two-step process parameters, film properties, and cell performance were studied. With the given selenization conditions, the efficiency of 12.5% for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 44 publications
(51 reference statements)
2
13
0
Order By: Relevance
“…Field studies, e.g., [11,16,30], have observed similar ranges of CGI and GGI atomic ratios to that which we reported in the current study. Park et al [16] investigated XRD patterns of CIGS thin films at substrate temperature ranging up to 600 • C. They found that all films which were grown at the temperature above 200 • C showed good crystallinity with FWHM value between 0.22 • and 0.35 • .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Field studies, e.g., [11,16,30], have observed similar ranges of CGI and GGI atomic ratios to that which we reported in the current study. Park et al [16] investigated XRD patterns of CIGS thin films at substrate temperature ranging up to 600 • C. They found that all films which were grown at the temperature above 200 • C showed good crystallinity with FWHM value between 0.22 • and 0.35 • .…”
Section: Discussionsupporting
confidence: 89%
“…Complex structure of Cu(In,Ga)Se 2 based solar cell requires a variety of technologies for particular layer fabrication to achieve high device efficiency. This is the reason why co-evaporation method is the most used one in the process of CIGS absorber fabrication [10][11][12] while chemical bath deposition (CBD) is a very common method of CdS buffer layer fabrication [13,14]. The application of optimal methods for each structure fabrication leads to the highest efficiency of the final device.…”
Section: Methodsmentioning
confidence: 99%
“…For the three-stage co-evaporated CIGS cell, as the thickness of the i-ZnO layer increased from 30 nm to 90 nm, the shunt resistance (R SH ) of the cell was significantly increased from 529.6 to 1126 Ω cm 2 , which results in the improvement of the V OC (from 0.467 V to 0.507 V), FF (from 61.8% to 66.3%) and conversion efficiency (from 10.1% to 11.8%), as displayed in Figure 12a. The improvement in the shunt resistance of the device with the i-ZnO thickness of 90 nm was due to the full coverage of the possible shunt paths within the CIGS/CdS layers with i-ZnO [31,49]. However, a further increas of i-ZnO thickness to 170 nm decreased the device performance parameters, especially the lowest J SC as the thick ZnO layer weakened the built-in field by spreading the space charge region [31].…”
Section: Resultsmentioning
confidence: 99%
“…The one-step and three-step processes have been studied extensively, and the films prepared by each method have been compared to determine which process produces the better CIGS films. The differences in band gap profiles, crystalline phases, growth mechanisms, and element distributions between films prepared by the one-step and three-step processes are reported in the literature. These reports showed that the films made with the three-step process had a slightly better electrical performance than those made with the one-step process due to the films made with the three-step process having a Cu-poor surface, a double-graded band gap, good stoichiometry control, and a large-grained absorber. Notably, a small-area CIGS-type solar cell based on three-step co-evaporation was recently demonstrated to have an efficiency surpassing 20% in the laboratory, which is better performance than that exhibited by CIGS cells produced by other processes as well as that of conventional multicrystalline Si devices …”
Section: Introductionmentioning
confidence: 95%